APPsα rescues CDK5 and GSK3β dysregulation and restores normal spine density in Tau transgenic mice - Baltissen, Danny; Bold, Charlotte S.; Rehra, Lena; Banićević, Marija; Fricke, Justus; Just, Jennifer; Ludewig, Susann; Buchholz, Christian J.; Korte, Martin; Müller, Ulrike C. (Frontiers in cellular neuroscience, 2023)
The Tau protein can be phosphorylated by numerous kinases. In Alzheimer’s disease (AD) hyperphosphorylated Tau species accumulate as neurofibrillary tangles that constitute a major hallmark of AD. AD is further characterized by extracellular Aβ plaques, derived from the β-amyloid precursor protein APP. Whereas Aβ is produced by amyloidogenic APP processing, APP processing along the competing non-amyloidogenic pathway results in the secretion of neurotrophic and synaptotrophic APPsα. Recently, we demonstrated that APPsα has therapeutic effects in transgenic AD model mice and rescues Aβ-dependent impairments. Here, we examined the potential of APPsα to regulate two major Tau kinases, GSK3β and CDK5 in THY-Tau22 mice, a widely used mouse model of tauopathy. Immunohistochemistry revealed a dramatic increase in pathologically phosphorylated (AT8 and AT180) or misfolded Tau species (MC1) in the hippocampus of THY-Tau22 mice between 3 and 12 months of age. Using a highly sensitive radioactive kinase assay with recombinant human Tau as a substrate and immunoblotting, we demonstrate an increase in GSK3β and CDK5 activity in the hippocampus of THY-Tau22 mice. Interestingly, AAV-mediated intracranial expression of APPsα in THY-Tau22 mice efficiently restored normal GSK3β and CDK5 activity. Western blot analysis revealed upregulation of the CDK5 regulatory proteins p35 and p25, indicating CDK5 hyperactivation in THY-Tau22 mice. Strikingly, AAV-APPsα rescued p25 upregulation to wild-type levels even at stages of advanced Tau pathology. Sarkosyl fractionation used to study the abundance of soluble and insoluble phospho-Tau species revealed increased soluble AT8-Tau and decreased insoluble AT100-Tau species upon AAV-APPsα injection. Moreover, AAV-APPsα reduced misfolded (MC1) Tau species, particularly in somatodendritic compartments of CA1 pyramidal neurons. Finally, we show that AAV-APPsα upregulated PSD95 expression and rescued deficits in spine density of THY-Tau22 mice. Together our findings suggest that APPsα holds therapeutic potential to mitigate Tau-induced pathology.